The Legal Protection of a Taxpayer During Tax Control According yo French Law - Budzikowski, Adam (Journal of Finance and Financial Law, 2014)
The article presents the legal basis for safeguards of controlled taxpayer’s rights in France comparing with similar solutions introduced in Polish tax law, including basic stands of the French and Polish jurisprudence. Therefore the article describes the application of rights and guarantees due to the division of tax control of enterprises as well as individuals. The author points also to the distinctive differences between Polish and French legal system as far as the protection of controlled taxpayers in both countries is concerned. Consequently, the article proves that the French legislation concerning mentioned rights is generally more beneficial to a controlled taxpayer than this existing in Poland.